CD38-driven NAD⁺ depletion governs crypt structure and barrier dysfunction in fluorouracil-induced colonic mucositis: From metabolic collapse to architectural remodeling - Elsayed A. Elmorsy; Rabab S. Hamad; Mohammed Alorini; Attia M. Gabr; Hamad Alsaykhan; Mostafa M. Khodeir; Mohamed F. Hindawy; Abdulaziz A. Alsalloom; Eman Mohamad El Nashar; Ahmed G. Hamad; Haytham Ali; Mohammed Ashraf Ali; et al. (Tissue and Cell, 2026)

Mitigating the impact of salinity and/or bisphenol A stress on the performance of the tomato crop by spraying with an algal extract of Ascophyllum nodosum L. - Mahmoud S. Abdelmoneim; Mohamed A. Ghazy; Elsayed E. Hafez; Sherif F. Hammad; Mona F.A. Dawood (Journal of Hazardous Materials, 2026)

Integrative analysis of genetic, biochemical, and microbial factors in camel calf diarrhea - Ahmed Elsayed; Amani A. Hafez; Mohamed T. Ragab; Marwa A. Fawzy; Adel M. El-Kattan; Ahmed I. Ateya (Veterinary Research Communications, 2026)
Diarrhea, though a clinical symptom, poses a major veterinary concern in camel calves due to high morbidity, mortality, growth retardation, and economic losses. This study investigated key bacterial enteropathogens, coding mutations, gene expression, and serum biochemical/antioxidant profiles in 35 healthy and 35 diarrheic camel calves. Fecal analysis using multiplex PCR identified Salmonella spp. , Clostridium perfringens, Proteus spp., and Escherichia coli with distinct virulence genes (e.g., papC, eaeA, iutA, hilA, sopB, plc, ureC). Diarrheic calves showed significant upregulation of immune-related genes (IL-8, IL-17, TLR4, TNFα, PIN1, IER3, UBD, TECPR1) and downregulation of antioxidant markers (PRDX2, SOD3, CAT, Nrf2), alongside sequence variations. Biochemically, diarrheic calves exhibited elevated serum AST, ALT, ALP, urea, creatinine, potassium, and MDA, with reduced glucose, total protein, calcium, phosphorus, magnesium, sodium, chloride, and SOD. These findings highlight the multifactorial etiology of diarrhea, linking bacterial virulence with metabolic and oxidative stress alterations, providing insights for targeted prevention and therapeutic strategies in camel herds.

Investigation of the Antibacterial Effectiveness of Hybrid Recombinant Bacteriocins Circular Enterocin and Pyocin L1 Derived from Pseudomonas aeruginosa and Enterococcus faecalis - Lina Jamil Abdel-Hafez; Mohamed Salah Basiouny; Islam Yousif Mostafa; Rehab Moustafa; Khaled Abuelhaded; Haytham Mohamed Abd-Elhalim; Abanoub A. S. Shaker; Hassan Elsayed; Olfat Salem; Amir Mahfouz Mokhtar Sarguos; Ahmed Hassan Ibrahim Faraag (Biochemical Genetics, 2026)

Chitosan reduces methane emissions and alters the phylogenetic affiliation of sampled methanogens in in vitro rumen fermentation - Marwa F. A. Attia; Amr E. El-Nile; Alaa M. A. Gad; Mohamed S. Moharam; Ahmed E. Kholif; Raed A. Aburawash; Elsayed E. Hafez; Sobhy M. A. Sallam (Environmental Science and Pollution Research, 2026)

Synthesis of waste-derived Tamarindus indica fruit (WD-TIF)-based polyphenol-encapsulated Ag-NPs: A next-generation sustainable antibiotic material - Gad Elsayed Mohamed Salem; Mohamed A. El-Sakhawy; Zahraa Zakarya Abd El-Hafez Mohammad; Shaymaa A. Mohamed; Neetu Talreja; Wirongrong Tongdeesoontorn; Mohammad Ashfaq (Biocatalysis and Agricultural Biotechnology, 2026)

An assessment of safe use and handling of agricultural pesticides by rural women in Abu Homous district of Egypt - Olfat S. Shahin; Atef M. K. Nassar; Nehal Abdel-Hakeem; Eman H. Radwan; Noha Nazeeh; Hafsa O. Hashem; Elsayed E. Hafez; Mamdoh T. Jamal; Zainab Shawky El-khalifa (International Journal of Tropical Insect Science, 2025)

Correction: Impact of Trichoderma, abscisic acid and polyamines on resistance tomato cultivars against M. incognita infection - Ibrahim A. Adss; Shokry R. Bayoumi; Hesham M. Heikal; Sherien E. Sobhy; Ahmed A. Saleh; Elsayed E. Hafez (Molecular Biology Reports, 2025)

Impact of Trichoderma, abscisic acid and polyamines on resistance tomato cultivars against M. incognita infection - Ibrahim A. Adss; Shokry R. Bayoumi; Hesham M. Heikal; Sherien E. Sobhy; Ahmed A. Saleh; Elsayed E. Hafez (Molecular Biology Reports, 2025)

Growth, physiological and molecular response of calcium and salicylic acid primed wheat under lead stress - Sherien E. Sobhy; Essam-Eldeen M. Abo-Kassem; Nasser A. Sewelam; Khalil M. Saad-Allah; Dalia G. Aseel; Ahmed A. Saleh; Elsayed E. Hafez (Molecular Biology Reports, 2025)

Utilizing safe biotic and abiotic alternatives to control botrytis californica, a new cryptic Species in the botrytis cinerea complex, and enhance strawberry quality and shelf life - Safaa A. M. Yousef; Sherien E. Sobhy; Ahmed A. Saleh; Elsayed E. Hafez (European Journal of Plant Pathology, 2025)

Using Sonchus oleraceus and Cichorium intybus extracts to enhance antiviral defense genes and trigger physiological parameters in tomato plants against tomato mosaic virus - Dalia G. Aseel; Marwa A. Samy; Mohamed Z.M. Salem; Elsayed E. Hafez; Ahmed Abdel-Megeed (Physiological and Molecular Plant Pathology, 2025)

Protective role of curcumin and selenium nanoparticles against aluminium chloride-induced hepatorenal toxicity in rats - Safaa M. Awad; Yasser A. Attia; Akaber T. Keshta; Shimaa H. Watad; Eman Rashad; Hassan Elsayed; Shams H. Abdel-Hafez; Aziza T. Fathy (Journal of Molecular Histology, 2025)

The supplementation of dietary black cumin (Nigella Sativa) seeds on performance, blood hematology, post-metabolic responses, antioxidant status, immunity, and inflammatory markers in pre-weaning calves - Mamdouh Elsayed; Khaled M. Al-Marakby; Sabry Abdel Hafez; Sameh A. Abdelnour (Tropical Animal Health and Production, 2025)
Pre-weaning feeding is critical for calf growth, laying the foundation for future productivity and health. Nigella sativa seeds (NS) are rich in bioactive compounds with numerous beneficial effects on health and various pharmacological properties. This study aimed to investigate the supplementation of NS powder on performance, post-metabolic attributes, immunity, antioxidant capacity, and inflammatory responses in pre-weaning Friesian calves. Twenty-four Friesian male calves at 4 days of age with a similar genetic line, weighing 33.67 ± 0.6 kg, were randomly allocated to three groups (8 animals per group). The study comprised three groups: a control group (NS0) receiving no supplementation, and two experimental groups received either 1% (NS1) or 3% (NS3) NS supplementation for 84 days. All levels of NS supplementation significantly improved the final body weight and body weight gain in a linear manner ( P < 0.001), while the highest total dry matter intake was observed in NS1 group (quadratic; P < 0.001). White blood cells (quadratic, P = 0.026), lymphocytes (quadratic, P = 0.012), and monocytes (linear effect; P = 0.001) significantly decreased, whereas red blood cells (linear; P = 0.004), hematocrit (linear; P = 0.002), mean corpuscular volume (MCV, linear; P = 0.003), and mean corpuscular hemoglobin concentration (MCHC, quadratic, P = 0.007), platelets (linear; P < 0.001) increased in calves fed NS. Feeding calves diets supplemented with NS led to a significant linear decrease in plasma creatinine and liver enzymes (AST and ALT) compared to the control diet ( P < 0.01). Calves fed 3% of NS in their diets had lower plasma cholesterol (linear; P < 0.001) and triglyceride levels (linear; P = 0.002) compared to calves in NS0 and NS1 groups. Polynomial analysis indicated a quadratic decrease in direct bilirubin ( P = 0.006), and a quadratic increase in immunoglobulin G (IgG, P = 0.014) and M (IgM, P = 0.032) in the calves fed the NS diet. All NS-supplemented groups showed a significant increase in IL-10 (linear; P < 0.001), TAC (linear; P = 0.006), and CAT (linear; P < 0.001), and a significant decrease in IL-4 levels (linear; P < 0.001) of the plasma of pre-weaning calves. As expected, pre-weaning calves fed diets containing NS (1% or 3%) exhibited a quadratic decrease in plasma malondialdehyde (MDA, P < 0.001) levels compared to those fed diets without NS. Our findings suggest that incorporating up to 3% Nigella sativa into pre-weaning calf diets can enhance growth, bolster immune function, and mitigate oxidative stress, offering a promising strategy for improving health and sustainability on dairy farms.

Enhanced Biochemical and Morphological Parameters in Eruca vesicaria by Applications of date-palm seed Extract - Doaa E. Elsherif; Gehad A. Ragab; Sherien E. Sobhy; Elsayed E. Hafez; Asmaa M. Khalifa (Journal of Soil Science and Plant Nutrition, 2025)
The current global context stimulating agroecology and green agriculture need to explore for the novel sustainable and eco-conscious methods for safeguarding plants. The aim of this study is to exploit the rich contents of date palm seeds (DPS) as an appropriate organic elicitor to boost growth and plant secondary metabolism in Eruca vesicaria . The seeds of DPS were utilized in the extraction process using distilled water to create an aqueous extract, which underwent phytochemical characterization. In a pot experiment, Eruca vesicaria seeds were soaked in serial doses (0, 20, 40, 80, and 120 g l ⁻¹) of DPS aqueous extract, and the 21-days old seedlings were collected. DPS extract analysis indicated adequate P and N contents, antioxidant compounds, and exhibited antioxidant activity. The primary components identified in the analysis of DPS were 2-Dodecenal, fatty acids and cyclopentane butyl-acid. Priming with DPS extract significantly improved its bio-stimulating capacity by enhancing fresh and dry biomasses, photosynthetic pigments, and primary metabolites in response to the optimal DSP concentration of 80 g l⁻¹. Stress biomarkers (H 2 O 2 and malondialdehyde (MDA)) were found in the ranges of water-primed control except for the highest dose of DPS extract (120 g l⁻¹). Further, priming with DPS extract increased the secondary metabolites (total phenolics and flavonoids) besides the activity of polyphenol oxidase (PPO), suggesting an enhanced cell redox system. The expression patterns of a series of specific key genes included in secondary metabolism modulation as, phenylalanine ammonia lyase ( PAL ), chalcone synthase ( CHS ), chalcone isomerase ( CHI ), flavonol synthase ( FLS ), and deoxyxylulose phosphate reductoisomerase ( DXR ), were activated following treatments with DPS extract. Overall, the present study underscores that the application of DPS extract can stimulate the growth and bioactive constituents of Eruca vesicaria , thus elevating its potential as a nutraceutical and medicinal value.

Effects of Pichia manshurica yeast supplementation on ruminal fermentation, nutrient degradability, and greenhouse gas emissions in aflatoxin B1 contaminated diets - Yosra Soltan; Amr Morsy; Mahmoud Elazab; Amr E. El-Nile; Nesrein Hashem; Mohamed Sultan; Younis Hamad; Gomaa Abo El Lail; Sohila Abo-Sherif; Nassra Dabour; Ehab Kheadr; Elsayed Hafez; et al. (Tropical Animal Health and Production, 2024)
Yeast feed additives present a natural approach for mitigating ruminal greenhouse gases (GHG) in an environmentally sustainable manner. This study aimed to isolate yeast strains from ruminal fluids capable of reducing GHG from Aflatoxin (AFB1) contaminated diets. Two isolates of Pichia manchuria (FFNLYFC1 and FFNLYFC2) were isolated and identified from the ruminal contents of dairy Zaraibi goats. An in vitro gas production assay was conducted to evaluate the impact of the yeast supplementations on a basal diet contaminated with AFB1 or not. The treatments were control (-AFB1; basal diet without supplements), control with AFB1 contamination (+ AFB1; basal diet containing 20 ppb AFB1), and yeast-supplemented diets (basal diet supplemented with Saccharomyces cerevisiae , and three treatments of P. manchuria [FFNLYFC1, FFNLYFC2, and their mixture at 1:1 ratio (Mix)]. High biological components were detected in abundance of both FFNLYFC1, FFNLYFC2 filtrates (e.g., diisooctyl phthalate). The Mix and FFNLYFC2 of P. manchuria reduced ( P < 0.05) methane by 23.5 and 20.8%, respectively, while only Mix inhibited carbon dioxide by 44% compared to the + AFB1 diet. All yeast diets improved ( P < 0.05) ammonia concentration, total protozoal and Entodinium spp. counts compared to + AFB1 diet. The Mix exhibited higher ( P < 0.05) values of ruminal degraded cellulose, total short-chain fatty acids, acetate and propionate compared to the individual isolates diets. The results suggest synergistic interactions among P. manshurica isolates, leading to enhanced ruminal fermentation and reduced GHG emissions while alleviating the adverse effects of AFB1. Therefore, we recommended the Mix of P. Manchuria as a novel feed additive to ruminant diets.

Physiological and Molecular Effects of Calcium and Salicylic Acid on Fusarium graminearum-Infected Wheat Seedlings - Sherien Sobhy; Essam‑Eldeen M. Abo‑Kassem; Khalil M. Saad‑Allah; Elsayed E. Hafez (Journal of Plant Growth Regulation, 2023)
Fusarium graminearum is among the most virulent pathogens attacking wheat plants and significantly lowering its production globally. The present work aims to shed light on the interactions between two priming solutions, calcium (Ca) or salicylic acid (SA), and F. graminearum inoculation depending on the growth rate, physiological attributes, and molecular responses in wheat seedlings. In a pot experiment, F. graminearum -pre-inoculated or inoculum-free sandy soil was used to germinate wheat kernels after priming them for 12 h in distilled water, 5-mM CaCl 2 , or 0.05-mM SA. The results demonstrated that F. graminearum inoculation decreased growth rate and chlorophyll content, but promoted carotenoids, stress markers (electrolytes leakage, lipid peroxidation, protein oxidation, hydrogen peroxide, and hydroxyl radical), antioxidant molecules (AsA, phenols, and flavonoids), osmolytes (GB, amino acids, and proline), and the antioxidant enzymes (CAT, GPX, SOD, PPO, and PAL). Additionally, the fungal infestation boosted the expression of CAT, GR, PR4, MT, and PCS genes. However, presoaking wheat kernels in Ca or SA solutions has contributed to mitigating the negative effects of fungal inoculation by restoring growth rate, chlorophyll content, and antioxidant capacity. It has also decreased the induced oxidative stress and downregulated the gene expression of F. graminearum -inoculated wheat seedlings. Consequently, by minimizing the negative repercussions of F. graminearum infestation, priming with Ca or SA could be used to appropriately stimulate growth and readjust the oxidative status of wheat seedlings.

Correction to: Potentials of mono‑ and multi‑metal ion removal from water with cotton stalks and date palm stone residuals - Heba Nagy; Manal Fawzy; Elsayed Hafez; Alaa El Din Mahmoud (Environmental Science and Pollution Research, 2023)

Potentials of mono- and multi-metal ion removal from water with cotton stalks and date palm stone residuals - Heba Nagy; Manal Fawzy; Elsayed Hafez; Alaa El Din Mahmoud (Environmental Science and Pollution Research, 2023)
In this work, cotton stalks ( Gossypium barbadense ) and date palm stones ( Phoenix dactylifera ) have been used as biosorbents to remove cadmium; Cd(II), lead; Pb(II), and zinc; Zn(II) from mono- and multi-solutions. Each biosorbent was characterized using SEM-EDX, and FT-IR. The findings showed that pH, dose, contact time, metal concentration, and particle size affect the treatment process. The adsorption pattern was Pb(II) > Cd(II) > Zn(II) for both biosorbents. The adsorption performance of cotton stalks was higher than that of date palm stones. The fitted maximum uptake capacities; q m of cotton stalks were higher than those of date palm stones. The maximum adsorption at optimum conditions of Pb(II), Cd(II), and Zn(II) with cotton stalks were 98%, 92.1%, and 78.9%, respectively, within 30 min. While the maximum adsorption of Pb(II), Cd(II), and Zn(II) with date palm stones were 94.6%, 76%, and 68.6%, respectively. Results confirmed the antagonistic effect of heavy metal removal at optimum conditions. Biosorbents could remove ~ 100% of the metal ions from real wastewater samples. Regeneration investigation revealed a successful reusability of both biosorbents for four cycles.

A review of recent innovative strategies for controlling mycotoxins in foods - Gamal M. Hamad; Taha Mehany; Jesus Simal-Gandara; Sarah Abou-Alella; Okon J. Esua; Mosaad A. Abdel-Wahhab; Elsayed E. Hafez (Food Control, 2023)

Expression profiling of HSP 70 and interleukins 2, 6 and 12 genes of Barki sheep during summer and winter seasons in two different locations - Raed A. Abu Rawash; Mahmoud A. Sharaby; Gamal El-Din A. Hassan; Alaa E. Elkomy; Elsayed E. Hafez; Salma H. Abu Hafsa; Mohamed M. I. Salem (International Journal of Biometeorology, 2022)
The objectives of this research were to contrast the expression values of heat shock protein (HSP70) and interleukins 2, 6 and 12 (IL 2, IL 6 and IL 12) genes in summer and winter in two different locations in Egypt (Alexandria zone and Matrouh zone) to deduce changes in thermo-physiological traits and biochemical blood metabolites of Barki sheep. A total of 50 ewes (20 in Alexandria and 30 in Matrouh) were individually blood sampled to determine plasma total protein (TP), Albumin, Globulin and Glucose constituents and T3, T4 and cortisol hormones. The thermo-physiological parameters of rectal temperature (RT, °C), skin temperature (ST, °C), Wool temperature (WT, °C), respiration rate (RR, breaths/min) and pulse rate (PR, beats/min) were measured for each ewe. Expressions of IL 2, IL 6, IL 12 and HSP 70 in summer and winter were analyzed along with thermo-physiological parameters and blood biochemical metabolites. In both locations, THI had significant effects on ST, WT, PR and RR, but not significant on RT. However, it had no significant effects on blood plasma metabolites and hormonal concentrations in the two locations in summer and winter. In Alexandria location, THI had negative significant effect on the expressions of IL-2 and IL-6 but positively affected on HSP70 genes in winter, while the expression of IL-12 gene was not affected by seasons, whereas in Matrouh zone, the effects of THI on the expressions of all tolerance genes were not significant. The results of the current study suggest that IL-2, IL-6 and HSP70 genes could be used as molecular markers for heat/cold stress.

Pre-soaking in Weed Extracts is a Reasonable Approach to Mitigate Fusarium graminearum Infection in Wheat - Sherien E. Sobhy; Essam-Eldeen M. Abo-Kassem; Nasser A. Sewelam; Elsayed E. Hafez; Dalia G. Aseel; Khalil M. Saad-Allah (Journal of Plant Growth Regulation, 2022)

Impact of dietary nano-zinc oxide on immune response and antioxidant defense of broiler chickens - Azza Hafez; Eldsokey Nassef; Mohamed Fahmy; Mabrouk Elsabagh; Abdelnasser Bakr; Elsayed Hegazi (Environmental Science and Pollution Research, 2020)

Effect of Hydrothermal Pretreatment on Volatile Fatty Acids Production from Thickened Waste Activated Sludge - Farokh laqa Kakar; Ehssan Hosseini Koupaie; Ahmed Shabir Razavi; Hisham Hafez; Elsayed Elbeshbishy (BioEnergy Research, 2020)

Iris yellow spot virus–induced chloroplast malformation results in male sterility - Ahmed Abdelkhalek; Sameer H Qari; Elsayed Hafez (Journal of Biosciences, 2019)

Improvement of nitrogen use efficiency in maize using molecular and physiological approaches - Dalia G. Aseel; Yehia Mostafa; Sanaa A. Riad; Elsayed E. Hafez (Symbiosis, 2019)

Compatible- and incompatible-type interactions related to defense genes in potato elucidation by Pectobacterium carotovorum - Said I. Behiry; Nader A. Ashmawy; Ahmed A. Abdelkhalek; Hosny A. Younes; Ahmed E. Khaled; Elsayed E. Hafez (Journal of Plant Diseases and Protection, 2017)

Chitinolytic Streptomyces griseorubens E44G enhances the biocontrol efficacy against Fusarium wilt disease of tomato - Younes M. Rashad; Abdulaziz A. Al-Askar; Khalid M. Ghoneem; Wesam I. A. Saber; Elsayed E. Hafez (Phytoparasitica, 2017)

Detection of New Point Mutations of BRCA1 and BRCA2 in Breast Cancer Patients - Moufida Bensam; Elsayed Hafez; Doaa Awad; Muhammad El-Saadani; Mahmoud Balbaa (Biochemical Genetics, 2014)

Sequencing and Utilization of the Gossypium Genomes - Andrew H. Paterson; Jun-kang Rong; Alan R. Gingle; Peng W. Chee; Elizabeth S. Dennis; Danny Llewellyn; Leon S. Dure; Candace Haigler; Gerald O. Myers; Daniel G. Peterson; Mehboob ur Rahman; Yusuf Zafar; et al. (Tropical Plant Biology, 2010)

Molecular characterization of soil microorganisms: effect of industrial pollution on distribution and biodiversity - Elsayed E. Hafez; Ebtesam Elbestawy (World Journal of Microbiology and Biotechnology, 2009)